The Gandhian Moment of Paul Ricoeur - Jahanbegloo, Ramin (Sophia, 2025)
Paul Ricoeur's approach to the problem of nonviolence is not only related to his religious background as a Christian philosopher, but also in relation with his readings of Mahatma Gandhi.